Space-time QAM wireless MISO systems employing differentially coded in-/out-FECC SCQICs over slow-fading Jakes scattering mobile radio links - Ardavan Rahimian; Farhad Mehran; Robert G. Maunder (The Journal of Engineering, 2014)
This study presents research that supplements and extends the previous works on design of space-time fully systematic unpunctured (FSU) serial concatenation of quadratic interleaved codes (SCQICs). The requirements for efficient design of the forward error correction (FEC) codecs motivated potential information-theoretic studies for enjoying the development of low-complex system components within the FEC encoder/decoder for securing the transmission reliability. Inspired by this motivation, this study not only provides design guidelines to achieve better bit error rate performance in terms of the major design factors of FSU-SCQICs, that is, component code constraint length and trellis structure, and FEC rate, but also estimates the gain gaps of different quadratic permutation (QP) structures in two crucial untouched aspects: (i) signal-to-noise ratio-region comparison on the optimality and (ii) investigation on the structural parameters of QPs, that is, cyclic shift and primitive factor.